Design of a Maize Sieving Machine. - Keshubi, Nice Alex (Kabale University, 2024)
This project presented the design and development of a reciprocating maize sieving machine, aimed at improving the efficiency of maize processing in agricultural operations. Traditional maize sieving methods are often labor-intensive and inefficient, resulting in significant post-harvest losses. This design introduces a mechanical solution that automates the sieving process, thereby reducing manual labor and enhancing processing speed. The reciprocating sieving machine features a crank slider mechanism specifically engineered to effectively separate maize from unwanted debris and broken grains. The reciprocating mechanism facilitates consistent and uniform movement of the maize through the sieve, promoting optimal separation and ensuring a higher-quality end product. Constructed from durable materials, the machine is designed to endure the demanding conditions of agricultural environments while being user-friendly and easy to maintain. This project addresses the pressing needs of maize processors by streamlining the sieving process. By improving efficiency and reducing labor costs, the machine supports local farmers in maximizing their yields and profitability. Future developments will focus on prototyping the design for larger-scale operations and exploring the integration of smart technologies for enhanced monitoring and automation. Overall, this reciprocating maize sieving machine represents a significant advancement in post-harvest processing techniques, contributing to increased food security and sustainability in agriculture